2016
DOI: 10.1002/jnr.23954
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells attenuate MRI‐identifiable injury, protect white matter, and improve long‐term functional outcomes after neonatal focal stroke in rats

Abstract: Cell therapy has emerged as a potential treatment for many neurodegenerative diseases including stroke and neonatal ischemic brain injury. Delayed intranasal administration of mesenchymal stem cells (MSC) after experimental hypoxia-ischemia and after a transient middle cerebral artery occlusion (tMCAO) in neonatal rats has shown improvement in long-term functional outcomes, but the effects of MSC on white matter injury (WMI) are insufficiently understood. In this study we utilized longitudinal T2W and diffusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 52 publications
0
27
0
Order By: Relevance
“…So far, most preclinical studies in the rodent model were performed for brain pathologies of the term newborn infant including hypoxic brain injury following perinatal asphyxia and neonatal stroke. Actual studies also evaluated the therapeutic potential of MSC therapy in periventricular leukomalacia and intraventricular hemorrhage [ 115 128 ]. For intraventricular hemorrhage, the contributions of inflammatory reaction to disease pathologies are well established and include brain damage by cell death induction of neurons and distortion of further myelination and gliosis [ 34 , 129 ].…”
Section: Further Areas Of Research With Exogenous Msc Applicationmentioning
confidence: 99%
“…So far, most preclinical studies in the rodent model were performed for brain pathologies of the term newborn infant including hypoxic brain injury following perinatal asphyxia and neonatal stroke. Actual studies also evaluated the therapeutic potential of MSC therapy in periventricular leukomalacia and intraventricular hemorrhage [ 115 128 ]. For intraventricular hemorrhage, the contributions of inflammatory reaction to disease pathologies are well established and include brain damage by cell death induction of neurons and distortion of further myelination and gliosis [ 34 , 129 ].…”
Section: Further Areas Of Research With Exogenous Msc Applicationmentioning
confidence: 99%
“…MSC treatment also stimulated neurogenesis, leading to better sensorimotor and social functions (70). In addition, van Velthoven et al (71,72) showed that intranasal MSC treatment at 3 days after neonatal stroke also significantly reduced infarct size and white and gray matter loss in newborn rats, leading to improved motor performance at 28 days after the infarct.…”
Section: Mesenchymal Stem Cell Therapymentioning
confidence: 99%
“…Our study suggests that the part of the answer can be found in the tissue treated by transplanted stem cells. The presence of transplanted stem cells supports regenerative events ( 13 , 14 , 17 ). For example, stroke increases the levels of Ripk1 , a necroptosis promotor, while transplanted medium and NSC oppose this process ( Figure 2A ).…”
Section: Discussionmentioning
confidence: 83%
“…There is growing evidence that stem cells transplantation measurably reduces the stroke area and accelerates recovery, both in preclinical ( 13 - 15 ) and clinical ( 16 , 17 ) trials. However, since the transplanted stem cells’ mechanisms of action in the injured tissue are not yet fully understood, we analyzed the influence of stem cell transplantation on the expression of genes involved in AIF-mediated cell death ( Aifm1 , Iduna , CypA ), necroptosis ( Ripk1 , Ripk3 , Mlkl ), and apoptosis ( Casp3 , Casp8 ).…”
mentioning
confidence: 99%